Setting the Record Straight: Essays on Ecclesiology, Missiology and Evangelism - Longwe, Hany (Luviri Press, 2021)
Cover -- Copyright page -- Title page -- Contents -- Chapter 1 - A Baptist Church Does Not Need a Pastor: A History of Theological Training for Convention Baptists in Malawi -- Bible Study and Sunday School, the Priesthood of all Believers and Evangelism -- Seminary Training -- Conclusion -- Chapter 2 - Theological Education in Baptist Churches in Eastern and Southern Africa -- Concept of Theological Education -- Two Perspectives of Theological Education in the Region -- Why Theological Education -- Local Church Training -- Bible School Training -- The Concept of Servant Leader -- Women and Theological Education -- Baptist Theological Education and Socio-religious Issues -- Quest for Relevant and Credible Theological Education -- Concept and Understanding of Accountability -- Conclusion -- Chapter 3 - Theology &amp -- Religious Studies and Development with Malawi in Mind -- Early African Christianity and Intellectual Pursuit -- Organization of the Universities in Malawi -- Theology and Religious Studies: Engagement and Benefits -- Political Transition 1992-1994 -- Research and Publications in Theology and Religious Studies -- Conclusion -- Chapter 4 - Missions across the Border: Baptist Convention of Malawi's Expansion into Neighbouring Countries -- Ministry of Seminary Students in Zambia and Zimbabwe -- Expansion into South Africa -- Ministry in Mozambique -- Conclusion -- Chapter 5 - The Matchona Contribution to Early Baptist Church History -- Labour Migration -- The Return to Malawi -- Stephen and Mary Galatiya -- Back Home -- McDonald W. and Agnes Kaduya -- J.M. and Helen Ng'oma -- Conclusion -- Chapter 6 - Kusadziwa Nkufa Komwe: The Baptist Theological Seminary of Malawi Fighting against HIV/AIDS -- The Beginning of the Fight -- Positive Developments -- The Seminary Concern for the Community -- Seminary Concern for its Students -- Conclusion.